2021
DOI: 10.1093/annweh/wxab070
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Methods for Surveillance of Occupational Exposure from Additive Manufacturing in Four Different Industrial Facilities

Abstract: 3D printing, a type of additive manufacturing (AM), is a rapidly expanding field. Some adverse health effects have been associated with exposure to printing emissions, which makes occupational exposure studies important. There is a lack of exposure studies, particularly from printing methods other than material extrusion (ME). The presented study aimed to evaluate measurement methods for exposure assessment in AM environments and to measure exposure and emissions from four different printing methods [powder be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 44 publications
(73 reference statements)
1
21
1
Order By: Relevance
“…More than 10 times the concentration (180,000-500,000 particles/cm 3 ) was found when measurements were performed close to the source. Broekhuizen et al suggested a nano reference value of 40,000 particles/cm 3 for nanoparticles with a density below 6 g/cm 3 (polymer particles have a density of 1-2 g/cm 3 ), which was exceeded in this study for all FDM and extrusion prints with no encapsulation or filter (23). Other techniques in this study, i.e., VP, PBF, and MJ, had concentrations below 20,000 particles/cm3 (PBF) or even below 5,000 particles/cm3 (VP and MJ), which is in agreement with other studies (24).…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…More than 10 times the concentration (180,000-500,000 particles/cm 3 ) was found when measurements were performed close to the source. Broekhuizen et al suggested a nano reference value of 40,000 particles/cm 3 for nanoparticles with a density below 6 g/cm 3 (polymer particles have a density of 1-2 g/cm 3 ), which was exceeded in this study for all FDM and extrusion prints with no encapsulation or filter (23). Other techniques in this study, i.e., VP, PBF, and MJ, had concentrations below 20,000 particles/cm3 (PBF) or even below 5,000 particles/cm3 (VP and MJ), which is in agreement with other studies (24).…”
Section: Discussioncontrasting
confidence: 55%
“…The methods used are described in detail in ref. 3. Briefly, hightime resolution particle emissions were measured using two different condensation particle counters (CPC): P-Trak 8,525 and Condensation Particle Counter 3,007 (TSI Incorporated, Minnesota 55,126 USA).…”
Section: Measurements Of Dust Particles and Gaseous Compoundsmentioning
confidence: 99%
“…As all work environments, AM work environments are controlled by occupational hygiene regulations to ensure the workers safety. Regarding airborne particles and chemicals, gravimetric or VOC analyzing techniques are today used to ensure that threshold limit values for specific compounds in air are not exceeded ( Ljunggren et al, 2019 ; Runström-Eden et al, 2021 ). However, it has been shown that the gravimetric measurements are not sufficient when assessing exposure-related health risks; mainly because particle sizes vary from 10 nm to 65 µm or larger, and due to different AM work activities entail different emissions and thereby exposure risks.…”
Section: Additive Manufacturing Emerging Safety Challenges: Particle ...mentioning
confidence: 99%
“…This indicates that airborne emissions associated with AM operations are variable, depending on printing and parts handling processes, raw materials, and ventilation characteristics. In addition, Runström-Eden et al (2021) have recently studied particle and VOC emissions from four different printing techniques: L-PBF, material extrusion (ME), MJ, and vat photopolymerization. The most significant emissions of particles in the size range 10 nm to 1 µm were found during ME printing.…”
Section: Additive Manufacturing Emerging Safety Challenges: Particle ...mentioning
confidence: 99%
See 1 more Smart Citation